Skills and Competitiveness: Can Pakistan Break Out of the Low-level Skills Trap? (The Iqbal Memorial Lecture) (The Pakistan Development Review, 2005)
The paper argues that if Pakistan is to survive and prosper under the competitive conditions of the new global economy, then it must move away from its overwhelming dependence on “cottonomics” into more technology- and knowledge-based products where global growth is concentrated. For this to happen, it must break out of the “lowlevel skills trap”, which is the result of the very low levels of education and skills of its work force. It then poses the question whether the development of a well-educated and skilled labour force is sufficient for the country to graduate from labour-intensive to higher value-added, skill-intensive, technologically advanced sectors. The paper argues that while this is essential, the real challenge is to change the mind-set and develop institutions which recognise the value of investing in people and provide dignity, respect, and a fair deal for working men and women.